SOCRATIC QUESTIONS USED BY THE SEVENTH SEMESTER STUDENTS OF ENGLISH DEPARTMENT OF FKIP NOMMENSEN IN SEMINAR CLASS - Fenty Debora Napitupulu (English Education Department at FKIP Nommensen University, 2020)
This study is aimed to know to find out the types of Socratic questions used by the students of seventh semester in English Department of FKIP UHN Medan. This research was conducted by descriptive qualitative where the subject is seventh English Department students in Nommensen University academic year 2019/2020 on Seminar Class and the data is students’questions. After analizing questions, it was found that Socratic questions used by the seventh semester of English students in FKIP UHN Medan are questions and clarification, questions that prope purposes, questions that probe assumptions, Question that Probe Information, Reason, Evidence, and Cause, Question about viewpoints or perspectives, Questions that Probe Implication and Consequences, Question about question, Question that Probe Concept, and Questions that probe Inferences and Interpretation. The most dominant is Question that Probe Information, Reason, Evidence, and Cause. It means that the students’ ability in making questions in seminar on ELT presentation is still on the level of getting information from the text, less to have capacity to view or to judge things from some other perspectives, less of preparing themselves reading the seminar paper before the presentation starts. The writer assumed that the students lack of reading.